2020
DOI: 10.1097/mao.0000000000002499
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Intracochlear Pressures From Laser Stapedotomy

Abstract: Hypothesis: Surgical manipulations during laser stapedotomy can produce intracochlear pressure changes comparable to pressures created by high-intensity acoustic stimuli. Background: New-onset sensorineural hearing loss is a known risk of stapes surgery and may result from pressure changes from laser use or other surgical manipulations. Here, we test the hypothesis that high sound pressure levels are generated in the cochlea during laser stapedotomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…To begin to fill this gap, we examined the effects of varying laser parameters on intracochlear pressure (P IC ) on human cadaveric specimens. This represents the continuation of a study investigating the risks during laser stapedotomy recently conducted and published by our laboratory 9 . This work demonstrated that surgical manipulations during laser stapedotomy create significant pressure changes within the cochlea.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…To begin to fill this gap, we examined the effects of varying laser parameters on intracochlear pressure (P IC ) on human cadaveric specimens. This represents the continuation of a study investigating the risks during laser stapedotomy recently conducted and published by our laboratory 9 . This work demonstrated that surgical manipulations during laser stapedotomy create significant pressure changes within the cochlea.…”
supporting
confidence: 57%
“…Similar measurements in living patients are difficult and ethically concerning. We have utilized comparable methods to provide quantitative estimates of resulting noise exposure from blast exposure, cochlear implant insertion, drill use, and laser use 9,10,14,28 . Our results reveal that P IC is significantly elevated during laser application and that pressures increase with increasing laser power.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Only freshly frozen TBs were used. The collected data from this group 17 , 18 will be denoted as “Colorado”. Because the point of measurement is different, we label this data as method “D”.…”
Section: Methodsmentioning
confidence: 99%